Você tem fome de quê?: consumo de alimento conveniente nas práticas alimentares de jovens adultos - Camacho, Anderson Pinheiro (2022)
There is a growing concern of people with food, with regard to the healthiness and sustainability of food and the social responsibility of the companies that sell it, which has been named as conscious consumption in this study. At the same time, the consumption of instant noodles has grown in the last 3 years in Brazil, the United States and globally. Several authors also state that there is a trend towards the growth of convenient food, which was defined in this study as convenient consumption. Given this scenario, from the perspective of Theories of Practice, the study aims to understand how instant noodles are consumed, associated with the practices of young Brazilian adults between 18 and 25 years old. For this, a qualitative method will be used, with interviews in the capital of São Paulo. This research aims to contribute to studies about the subject in Brazil, where there is a shortage of works in this area, even with the strong growth of convenient consumption in recent years and the trend for the next. In addition to contributing with important findings for companies that operate or intend to operate with convenient food and, also, it´s a social contribution, as conscious and convenient consumption is a paradox for society today.